A review on the utilization of ceramic tile waste as cement and aggregates replacement in cement based composite and a bibliometric assessment - Tanash, Alaa Omar; Khairunisa, Muthusamy; Rajan, Jose; Muhammad Ashraf, Fauzi; Budiea, A. M. A.; Gul, Jokhio (Elsevier Ltd, 2023)
The scientific community recognizes that the depletion of natural resources and solid waste management pose inherent challenges in building material production and disposal, particularly in concrete manufacture and deconstruction. Recycling and reusing construction waste is proposed as a solution to these issues in the literature. Repurposing waste materials as additives in concrete represents an alternative approach. For instance, ceramic tile waste (CTW) may replace a portion of the aggregate and cement used in concrete. This study extensively examines the literature on cement-based composites that utilize CTW in lieu of cement and aggregate. A thorough evaluation of mechanical, durability, and fresh properties is conducted. The physical and chemical attributes of CTW are based on extensive scientific research. Prior studies suggest that the use of ceramic tile aggregate (CTA) to concrete in the appropriate proportions could enhance its durability and strength. Finely ground ceramic tile powder (CTP) with high silica content can potentially enhance the strength and durability of concrete, according to prior research studies. The impact of CTP on the chemical resistance, drying shrinkage and fire resistance abilities of concrete are subsequently evaluated. Employing waste materials as a concrete component in a circular economy to promote environmental protection and the development of sustainable cities and communities has received broad support from the academic community.